Phylogenomics and Coalescent Analyses Resolve Extant Seed Plant Relationships - Xi, Zhenxiang (Public Library of Science, 2013)
The extant seed plants include more than 260,000 species that belong to five main lineages: angiosperms, conifers, cycads, Ginkgo, and gnetophytes. Despite tremendous effort using molecular data, phylogenetic relationships among these five lineages remain uncertain. Here, we provide the first broad coalescent-based species tree estimation of seed plants using genome-scale nuclear and plastid data By incorporating 305 nuclear genes and 47 plastid genes from 14 species, we identify that i) extant gymnosperms (i.e., conifers, cycads, Ginkgo, and gnetophytes) are monophyletic, ii) gnetophytes exhibit discordant placements within conifers between their nuclear and plastid genomes, and iii) cycads plus Ginkgo form a clade that is sister to all remaining extant gymnosperms. We additionally observe that the placement of Ginkgo inferred from coalescent analyses is congruent across different nucleotide rate partitions. In contrast, the standard concatenation method produces strongly supported, but incongruent placements of Ginkgo between slow- and fast-evolving sites. Specifically, fast-evolving sites yield relationships in conflict with coalescent analyses. We hypothesize that this incongruence may be related to the way in which concatenation methods treat sites with elevated nucleotide substitution rates. More empirical and simulation investigations are needed to understand this potential weakness of concatenation methods.